Reproductive tract infections and sexually transmitted diseases in a rural area of Bangladesh: insights for action from research - Hashima-E-Nasreen (BRAC Research and Evaluation Division (RED), 2019)
Objectives: The study aimed· to assess the magnitude of problem associated with RTis/STDs in rural Matlab, Bangladesh. It estimates the prevalence and attempts to explore the risk indicators for RTis and STDs among people of different age group within the existing socio-cultural context. Methods: A combination of qualitative and quantitative research methods was utilized. Indepth interview, focus group discussion, and a cross-sectional survey of randomly selected men, women, and adolescent boys and girls were the main methods employed. The ICDDR, B surveillance database provided the sampling frame. Results: About 19% of people in Matlab have had STDs. Lack of awareness, risky sexual behaviour, lack of accessibility and availability of adequate services, traditional and unhygienic health practices, absence of programme efforts, and illiteracy and poverty were the prevalent soia-cultural factors that potentially has put people at risk of RTis, STDs as well as HIV/AIDS epidemic. The bridge between non-commercial and commercial partners was laid by men whom work in urban area push up the likelihood of infection from the high risk (urban) to low risk group of women in the village. Risky sexual behaviour was also prevalent among adolescents. Partners' communication and treatment seeking behaviour were found to be very poor among adults and not at all among adolescents. There is a need for collaborative action addressing rural people's riskassessment component. Conclusion: To avert the situation, a holistic approach should be adopted with greater emphasis on RTI/STD control and prevention together with human relationship, communication , gender, family interaction and socio-economic status that would determine the nature and extent of people's risk and vulnerabilities. Because of the sensitivity of issue, it is important to think about how to achieve community acceptance. so that programme can expand and sustain itself.